2020
DOI: 10.1111/ejn.14969
|View full text |Cite
|
Sign up to set email alerts
|

The effects of microglia‐ and astrocyte‐derived factors on neurogenesis in health and disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 230 publications
(282 reference statements)
0
75
0
Order By: Relevance
“…Pharmacological intervention with compounds that show anti-inflammatory properties have demonstrated the neurodegenerative role of glial cytokines, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), following OP poisoning. However, it is important to mention that the secretion of other microglia- and astrocyte-derived factors that promote neurogenesis [ 37 ] may also contribute as a restorative effect following OP-induced seizure. Microglia have been implicated in the suppression of excess proliferation of neural stem cells and the inhibition of the formation of abnormal neural circuits by phagocytosis of adult-born granule cells in the epileptic dentate gyrus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological intervention with compounds that show anti-inflammatory properties have demonstrated the neurodegenerative role of glial cytokines, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), following OP poisoning. However, it is important to mention that the secretion of other microglia- and astrocyte-derived factors that promote neurogenesis [ 37 ] may also contribute as a restorative effect following OP-induced seizure. Microglia have been implicated in the suppression of excess proliferation of neural stem cells and the inhibition of the formation of abnormal neural circuits by phagocytosis of adult-born granule cells in the epileptic dentate gyrus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, microglia are innate immune cells in the brain, while astrocytes are the key participants of central nervous system immune responses [ 47 , 48 ]. It has been reported that the activation of microglia was obviously increased in depression patients, and nerve damage induced by microglia is considered to be an important mechanism of depression [ 49 51 ]. In addition, some antidepressants, such as minocycline, can play a protective role by inhibiting the activation of microglia, oxidative stress, and inflammation [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mitochondria-derived from astrocytes rescue neurons whose mitochondria are damaged by stroke [ 10 ]. One mechanism by which they do this may be by secreting factors important for neurogenesis and neural function [ 37 ]. The treatment of culture medium of astrocytes from Fmr1 KO mice increases the percentage of large-size neurospheres but not the number of neurospheres, indicating that proteins secreted by astrocytes affect neural proliferation and differentiation [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%